2018
DOI: 10.3389/fneur.2018.01042
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Pre-stroke Psychosis and Post-stroke Levels of Health, Resource Utilization, and Care Process: A Register-Based Study

Abstract: Background: While approximately one percent of the global population is formally diagnosed with psychosis or schizophrenia, the actual number is expected to be significantly higher. These patients often consume more healthcare resources and have poorer somatic health. In this study, we analyze potential differences in health, resources, and care process between stroke patients with and without a previous diagnosis of psychosis or schizophrenia.Methods: Ischemic stroke patients from seven regions in Sweden were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As psychosis, and treatment for psychosis, is a risk factor for later stroke (Li et al, 2014; Marto et al, 2021), stroke in patients with a preceding history of psychosis is also likely to be an important contributory factor to co-prevalence. We also note here that initial studies report that patients with psychosis who later experience stroke have worse outcomes and are less likely to receive equitable care (Kisely et al, 2009; Willers et al, 2018) including timely invasive interventions (Nielsen et al, 2021). Taken together, this evidence suggests that stroke and psychosis may be highly disabling, but is under-recognised and likely under-served by existing services.…”
Section: Discussionmentioning
confidence: 78%
“…As psychosis, and treatment for psychosis, is a risk factor for later stroke (Li et al, 2014; Marto et al, 2021), stroke in patients with a preceding history of psychosis is also likely to be an important contributory factor to co-prevalence. We also note here that initial studies report that patients with psychosis who later experience stroke have worse outcomes and are less likely to receive equitable care (Kisely et al, 2009; Willers et al, 2018) including timely invasive interventions (Nielsen et al, 2021). Taken together, this evidence suggests that stroke and psychosis may be highly disabling, but is under-recognised and likely under-served by existing services.…”
Section: Discussionmentioning
confidence: 78%
“…se). [12][13][14][15] The research database consisted of data from patients with acute stroke 2007-2012, identified in patient administrative systems (PAS) from seven Swedish regions (Jämtland-Härjedalen, Östergötland, Dalarna, Uppsala, Skåne, Stockholm and Västra Götaland), covering approximately 60% of all registered strokes annually in Sweden. PAS contain information on diagnosis and procedure codes related to all healthcare activities registered within the region.…”
Section: Materials and Methods Sveus Stroke Research Databasementioning
confidence: 99%
“…The association between schizophrenia and stroke case fatality is less well understood, with some studies suggesting an increase 3 10 11 and others no difference 12 or a decrease 13 in poststroke mortality in those with schizophrenia. Prestroke antipsychotic use has been associated with an increased risk of severe stroke, which in turn could contribute to poststroke mortality in those with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Following myocardial infarction, the excess mortality observed in people with schizophrenia is in part explained by lower use of guideline-recommended interventions and medications. 15–20 Previous research suggests that people with schizophrenia are also less likely to receive interventions for acute stroke care and secondary prevention, 12 but it is not known whether such differences in care explain variations in stroke case fatality.…”
Section: Introductionmentioning
confidence: 99%